2015
DOI: 10.1107/s2052520615018739
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic flexibility of porous materials; theory, modelling and the flexibility window of the EMT zeolite framework

Abstract: Framework materials have structures containing strongly bonded polyhedral groups of atoms connected through their vertices. Typically the energy cost for variations of the inter-polyhedral geometry is much less than the cost of distortions of the polyhedra themselves -as in the case of silicates, where the geometry of the SiO 4 tetrahedral group is much more strongly constrained than the Si-O-Si bridging angle. As a result, framework materials frequently display intrinsic flexibility, and their dynamic and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 51 publications
8
21
0
Order By: Relevance
“…This mirrors the predictions of Fletcher et al . [ 33 ] from geometric simulations and our previous high-pressure study of the EMT framework containing the 18C6 molecule [ 34 ]. However, there is a discrepancy as the flexibility of the filled and empty EMT frameworks is identical, unlike that seen herein for the FAU framework.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mirrors the predictions of Fletcher et al . [ 33 ] from geometric simulations and our previous high-pressure study of the EMT framework containing the 18C6 molecule [ 34 ]. However, there is a discrepancy as the flexibility of the filled and empty EMT frameworks is identical, unlike that seen herein for the FAU framework.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, this leads to a decrease in compressibility as a function of pressure. However, other work has shown how the intrinsic flexibility window and compression of the EMT framework is unperturbed by the occlusion of 18-crown-6 ether (18C6) [ 33 , 34 ]. This is of particular interest, as 18C6 is used as an organic additive in the preparation of EMT-type zeolites like EMC-2 [ 35 , 36 ], where synthesis without 18C6 has not been achieved [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on a siliceous faujasite structure, we have distinguished the intrinsic window, governed by the framework alone, from the extrinsic window controlled by interactions with extra-framework content inside small sodalite (SOD) cages [ 10 ]. Interestingly, we found that this is not always the case, as we have shown with crown ether and without in larger t-wof and t-wou cages in EMC-2 zeolite [ 11 ]. The geometric simulation approach is not limited to tetrahedral systems, and has, for example, been applied successfully to networks of regular and Jahn–Teller distorted octahedra in manganite perovskites [ 12 14 ].…”
Section: Introductionmentioning
confidence: 84%
“…Figure 2 shows the variation in lattice parameters of the filled and empty (i.e., with and without 18C6) zeolite EMC-2 as a function of pressure. The flexibility window of the EMT framework obtained from geometric simulations, which suggest the window to be identical for both the empty and 18C6 filled zeolite EMC-2, is overlaid for comparison [25]. This comparison indicates that our measurements were performed well within the window boundaries and, consequently, no distortions of the TO4 tetrahedra are anticipated over the range of pressures studied.…”
Section: Introductionmentioning
confidence: 83%
“…This strongly suggests a competition between the FAU and EMT phases during crystallisation. Simulation results further suggest that the macrocation influences the free-energy landscape during the crystallisation process rather than acting as a geometric template [25]. [28] are highlighted.…”
Section: Introductionmentioning
confidence: 89%